Ethnomedicinal Plants Used by the Dura Tribe in Lamjung District, Nepal - Nemkul, Chandra Mohini; Ghimire, Aayushna (Journal of Plant Resources, 2025)
An ethnobotanical survey was conducted to document medicinal plants used by the Dura tribe for the treatment of various ailments in Neta, Madhyanepal municipality, Lamjung District, Nepal. Field visits were carried out from October 2022 to April 2023 to collect ethnobotanical data. Data were gathered from 56 key informants using semi-structured interviews, un-structural interviews, group discussions, and questionnaires. The study area is rich in ethnic diversity, encompassing a range of ethnic groups such as Gurung, Dura, Brahmin, Chhetri, Magar, Damai, Kami, Sarki, etc. A total of 73 plant species belonging to 45 families, used to treat 64 different ailments, were recorded. The factor of informant consensus (FIC) for muscular/skeletal disease category had the highest value. The results showed that four plant species namely: Calotropis gigantea, Drynaria quercifolia, Hoya lanceolata and Periploca graeca were culturally important to the Duras for the treatment of muscular sprain and bone fracture. Herbs were the most commonly used plant for medicine followed by tree and shrub. Leaves were the most frequently used plant parts, and the majority of plants were used in the form of juice. Wild plant species accounted for 63% of the medicinal plants used. Although the Duras are a marginalized tribe, they possess huge indigenous knowledge about medicinal plants. Moreover, phytochemical analysis of culturally valued plants within the Dura community should be conducted to validate this knowledge scientifically.